The importance of adopting blockchain technology into financial accounting practices - Hassanudin, Abdul Fatah; Saepuloh, Asep; Nurjaman (Outline Publisher, 2025)
In the past decade, blockchain technology has developed quickly and gained the attention of many people, especially in the subject of accounting. The purpose of this study is to determine the benefits and challenges related to blockchain technology in the field of accounting. This study uses an extensive overview of the literature as its approach to research. Blockchain technology provides a decentralized, secure, and transparent framework for maintaining data. The idea that blockchain allows for things to be more open and accountable shows how useful it is in accounting. Using blockchain, companies can make their financial statements more accurate and clear, which will make investors and other stakeholders more likely to trust them. However, using blockchain in accounting also comes with a lot of problems, such as following the rules, keeping data safe, and the costs of setting it into place. As a result, businesses need to think carefully before using the blockchain technology in their financial management.